Research Note: Comparative evaluation of pathogenicity in SPF chicken between different subgroups of H5N6 high pathogenicity avian influenza viruses - Yoon-Gi Baek; Yu-Na Lee; Ra Mi Cha; Min-Ji Park; Youn-Jeong Lee; Choi‐Kyu Park; Eun-Kyoung Lee (Poultry Science, 2024)
ABSTRACT: Since 2014, periodic outbreaks of high pathogenicity avian influenza (HPAI) caused by clade 2.3.4.4 H5 HPAI virus (HPAIV) have resulted in huge economic losses in the Korean poultry industry. During the winter season of 2016–2017, clade 2.3.4.4e H5N6 HPAIVs classified into 5 subgroups (C1–5) were introduced into South Korea. Interestingly, it was revealed that the subgroup C2 and C4 viruses were predominantly distributed throughout the country, whereas detection of the subgroup C3 viruses was confined in a specific local region. In the present study, we conducted comparative evaluation of the pathogenicity of viruses belonging to subgroups C2 and C3 (H15 and HN1 strains) in specific pathogen-free (SPF) chickens, and further compared them with previously determined pathogenicity of subgroup C4 (ES2 strain) virus. The HN1 strain showed lower viral replication in tissues, less transmissibility, and higher mean chicken lethal dose than the H15 and ES2 strains in SPF chickens. Considering that the HN1 strain has a different NS gene segment from the H15 and ES2 strains, the reassortment of the NS gene segment likely affects their infectivity and transmissibility in chickens. These findings emphasize the importance of monitoring the genetic characteristics and pathogenic features of HPAIVs to effectively control their outbreaks in the field.